2009
DOI: 10.2478/s11532-009-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Organic/Inorganic bioactive materials Part II: in vitro bioactivity of Collagen-Calcium Phosphate Silicate/Wollastonite hybrids

Abstract: Abstract:In the present study, novel hybrid materials of Collagen (C) and Calcium Phosphate Silicate/Wollastonite (CPS/W) were synthesized.The CPS/W ceramic was prepared via polystep sol-gel method. The dissolution test of CPS/W ceramic was filled with TRIS-HCl buffer. FTIR depicts that hydroxyl carbonate apatite (OHCO 3 HA) was observed after 3 days of immersion in TRIS-HCl buffer. Biohybrids of C-CPS/W were produced from diluted hydrochloric acid collagen type I and ceramic powder with different ratios of C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…The emergence of these two peaks could be due to the absorption of CO 2 from atmosphere even after thermal treatment. A similar observation has been reported with calcium phosphate silicate/wollastonite (12), and hence, storage in dessicator is advised. XRD patterns (Fig.…”
Section: Characterization Of Sss Powdermentioning
confidence: 55%
“…The emergence of these two peaks could be due to the absorption of CO 2 from atmosphere even after thermal treatment. A similar observation has been reported with calcium phosphate silicate/wollastonite (12), and hence, storage in dessicator is advised. XRD patterns (Fig.…”
Section: Characterization Of Sss Powdermentioning
confidence: 55%
“…glass-reinforced HA/polyacrylate 1068 as well as collagen 1069 and gelatin 1070 calcium phosphate silicate/wollastonite biocomposites. HA/glass biocomposites can be prepared by simple sintering of appropriate HA/glass powder mixtures.…”
Section: Injectable Bone Substitutes (Ibs)mentioning
confidence: 99%
“…First of all, in the spectrum of pure collagen (data are not shown here), the amide I peak centered at 1656 cm -1 predominantly corresponds to the C=O stretch vibration [12]. From the other studies, the amide I band in a bone spectrum is representative of the collagen content and structure [18].…”
Section: Results and Discussionanalysis Of The Composites Before In Vmentioning
confidence: 70%
“…We observed that the prepared ceramics were in vitro bioactive for different periods of time. On this base we have prepared in vitro bioactive composites with some biodegradable polymers without [12][13][14][15] and with [16] cross-linkage.…”
Section: Introductionmentioning
confidence: 99%